Teaching and learning of Arabic script (Jawi) at Malaysian elementary school - Abd. Rahman, Akmal Khuzairy (s.n, 2012)
The research is a part of a paper entitled : The teaching of Arabic Script in Malaysian Education System, which is intended to be presented during the coming Sub Regional Symposium on the Incorporation of the Languages of Asian Muslim Peoples into the Standardised Quranic Script Project (SQSP) in Kuala Lumpur.